Ligand Binding in Hemoglobin: the Work of Quentin H. Gibson - Kresge, Nicole (American Society for Biochemistry and Molecular Biology, 2009)
Oxygen Binding and Subunit Interaction of Hemoglobin in Relation to the Two-state Model (Gibson, Q. H., and Edelstein, S. J. (1987) J. Biol. Chem. 262, 516–519) Ligand Recombination to the α and β Subunits of Human Hemoglobin (Olson, J. S., Rohlfs, R. J., and Gibson, Q. H. (1987) J. Biol. Chem. 262, 12930–12938)